2016
DOI: 10.1016/j.parkreldis.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

An unexpectedly high rate of revisions and removals in deep brain stimulation surgery: Analysis of multiple databases

Abstract: Introduction Deep brain stimulation (DBS) is an established therapy for movement disorders, and is under active investigation for other neurologic and psychiatric indications. While many studies describe outcomes and complications related to stimulation therapies, the majority of these are from large academic centers, and results may differ from those in general neurosurgical practice. Methods Using data from both the Centers for Medicare and Medicaid Services (CMS) and the National Surgical Quality Improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…Among the remainder device complications and infections were the main reasons. The device complications could not be specified in this study . Our own data demonstrate a high and yet underestimated incidence of short circuits as an important technical dysfunction, which may have contributed to the high revision rate.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Among the remainder device complications and infections were the main reasons. The device complications could not be specified in this study . Our own data demonstrate a high and yet underestimated incidence of short circuits as an important technical dysfunction, which may have contributed to the high revision rate.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the detection of a short circuit needs careful evaluation and follow‐up but does not necessitate surgical revision in all patients. These considerations are of particular interest since a recent analysis of multiple North American databases revealed an unexpectedly high rate of revisions and removals in DBS surgery between 15 and 34% . The reasons for revisions/removals could not be identified in detail but suggested improper targeting or lack of therapeutic effect in up to half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 It should, however, be noted that a recent study of a large national registry including over 28,000 cases revealed that the incidence of revisions and removals of DBS electrodes was greater than 15%, which the authors considered might be due to improper targeting or lack of therapeutic effect. 25 In addition, a recent study showed that complication rates could be reduced with sophistication of surgical techniques. 6,14 These reports may have addressed the importance of the subspecialty training prior to opening a DBS practice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent US study reported an exceedingly high rate of lead relocation due to suboptimal placement in up to 16% of DBS procedures. 4 In other words, up to 1 in 6 DBS procedures are revision operations, performed to rectify a targeting error that could have been avoided or immediately rectified during the initial procedure. This finding underscores the importance of obtaining routine postoperative stereotactic CT or MR imaging, irrespective of any clinical or neurophysiological observations made during surgery.…”
mentioning
confidence: 99%